PENGARUH GAYA KEPEMIMPINANA DAN MOTIVASI KERJA TERHADAP KINERJA GURU MELALUI KEPUASAN KERJA (STUDI PADA SMK NEGERI 5 JEMBER) - Sutikno Sutikno; Bagus P. Yudha; Ridwan Iskandar (RELASI : JURNAL EKONOMI, 2016)
To increase the productivity of human resources in an organization, aspectsof job satisfaction and performance has always been a very important discussion,because both are two important aspects in achieving organizational goals. This studyaims to determine whether there is influence of leadership style and work motivationon teacher performance SMK Negeri 5 Jember through job satisfaction. Thepopulation in this study are all teachers PNS SMK Negeri 5 Jember totaling 99people. Sampling using census method so that the sample in this study amounted to99 people. Data were analyzed using Path Analysis. The test results of path analysisshowed that: In the first track, style of leadership and motivation have a significanteffect on performance. On the second track, motivation significant effect onperformance while the two other variables namely; leadership style and jobsatisfaction did not significantly affect the performance of teachers SMK Negeri 5Jember. The results of this analysis also states that the style of leadership, motivationand job satisfaction influence simultaneously on teacher performance. Workmotivation is a variable that has a dominant influence on the performance ofteachers.